First Year After Stroke: An Integrated Approach Focusing on Participation Goals Aiming to Reduce Depressive Symptoms - Graven, Christine; Brock, Kim; Hill, Keith; Cotton, Sue; Joubert, Lynette (Lippincott Williams & Wilkins, 2016)
© 2016 American Heart Association, Inc. BACKGROUND AND PURPOSE: Depression is a common issue after stroke. A focus on assisting people to achieve their personal participation goals may reduce levels of depression. The aim of this study was to investigate the effectiveness of a person-centered, integrated approach on facilitating goal achievement in the first year poststroke on depressive symptoms. METHODS: This study was a randomized controlled trial that addressed ways to enhance participation in patient-valued activities and intermittently screen for adverse sequelae postdischarge from rehabilitation. Collaborative goal setting was undertaken in both groups at discharge from inpatient rehabilitation. The control group received standard management as determined by the treating team. In addition, the intervention group received a multimodal approach, including telephone contacts, screening for adverse sequelae, written information, home visits, review of goal achievement, and further referral to relevant health services. The main outcome measure was depressed mood, measured by the 15-item Geriatric Depression Scale. RESULTS: One hundred ten participants were recruited. No group differences were identified at baseline on any demographic and clinical variables. Using multiple linear regression analysis, there was a significant difference between the 2 groups with respect to the severity of depressive symptoms at 12 months poststroke (R2=0.366; F (6, 89)=8.57; P<0.005), with the intervention group recording lower depressive scores. CONCLUSIONS: This model of community-based rehabilitation proved effective in reducing poststroke depressive symptoms. An integrated approach using pursuit of patient-identified activities should form part of routine poststroke management.